Herding scientists a story of failed reform at the CDC - Whitford, Andrew ca. 20./21. Jh (Cambridge University Press, 2022)
When politicians reshape public health agencies, scientists resist changes and, if possible, leave. Those shifts make it harder for agencies to fight future public health threats. This Element focuses on the tension between scientists and managerial control in the policy process, both conceptually and empirically. It centers on a failed attempt to reorganize the United States Centers for Disease Control and Prevention. Because many of the gains in longevity and health quality result from the work of public health agencies, public health scientists and practitioners are the frontline producers of public health
Title from publisher's bibliographic system (viewed on 07 Apr 2022)
Keywords: Centers for Disease Control and Prevention (U.S.); Medical policy / United States; Medical scientists / United States